Fire exclusion changes belowground bud bank and bud-bearing organ composition jeopardizing open savanna resilience - Bombo, Aline Bertolosi [UNESP]; Appezzato-da-Glória, Beatriz; Fidelis, Alessandra [UNESP] (Springer Nature, 2022)
Belowground bud bank regeneration is a successful strategy for plants in fire-prone communities. It depends on the number and location of dormant and viable buds stored on belowground organs. A highly diverse belowground bud-bearing organ system maintained by a frequent interval of fire events guarantees the supply of a bud bank that enables plants to persist and resprout after disturbance. We investigated how different fire exclusion and fire frequencies, affected the herbaceous layer in tropical savannas, by assessing belowground persistence and regeneration traits. Contrary to our hypothesis, we found that under a shorter fire exclusion period, the total bud bank increased at a lower fire frequency. But sites at longer fire exclusion and infrequent fire, the bud bank was smaller the longer the period since the last fire. However, the major shift was concerning organ diversity since fire exclusion was more related to loss of belowground diversity rather than decreasing of the belowground bud bank size. Furthermore, fire-associated bud-bearing structures like xylopodia disappeared in the fire suppressed areas, whereas clonal organs, such as rhizomes, developed in the bud bank. By quantifying belowground bud bank traits under different fire histories, we highlight the importance of the local fire regime on the composition of the belowground plant components, which can affect the tropical savanna aboveground plant community. Given that, loss of the belowground bud-bearing component of the plant community will have a direct effect on vegetation regeneration in post-fire environments, and consequently, on plant community resilience.
Keywords: Belowground bud-bearing organs; Fire frequency; Open savannas; Resprouting; Time since last fire